2022
DOI: 10.3390/cimb44090293
|View full text |Cite
|
Sign up to set email alerts
|

PADI4 Haplotypes Contribute to mRNA Expression, the Enzymatic Activity of Peptidyl Arginine Deaminase and Rheumatoid Arthritis Risk in Patients from Western Mexico

Abstract: Citrullination is catalyzed by the peptidyl arginine deiminase 4 (PAD4) enzyme, encoded by the PADI4 gene. Increased PAD4 activity promotes the onset and progression of rheumatoid arthritis (RA). This study aimed to evaluate the association of PADI4 haplotypes with RA risk, mRNA expression, and the PAD4 activity in patients with RA from Mexico. Methodology: 100 RA patients and 100 control subjects (CS) were included. Genotyping was performed by PCR-RFLP method, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Likewise, GTG-positive individuals had worse periodontal clinical parameters. Previous in vitro studies using leukocytes from individuals with RA have reported greater activity of the PAD4 enzyme and greater affinity for calcium ions in carriers of the positive GTG haplotype (Hung et al, 2007;Matuz-Flores et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
See 4 more Smart Citations
“…Likewise, GTG-positive individuals had worse periodontal clinical parameters. Previous in vitro studies using leukocytes from individuals with RA have reported greater activity of the PAD4 enzyme and greater affinity for calcium ions in carriers of the positive GTG haplotype (Hung et al, 2007;Matuz-Flores et al, 2022).…”
Section: Discussionmentioning
confidence: 87%
“…Other studies have also revealed an association between ACPAs and the presence of PADI4 polymorphisms (Gandjbakhch et al, 2009; Guzmán‐Guzmán et al, 2015). Recently, increased PADI4 expression was reported in Mexican RA individuals carrying the GTG haplotype (Matuz‐Flores et al, 2022). In line with our data, an increase in mRNA and higher levels of PAD4 transcripts have been detected in individuals carrying the GTG haplotype, which may lead to an increase in the release of citrullinated peptides that act as autoantigens (Guzmán‐Guzmán et al, 2015; Hill et al, 2003; Matuz‐Flores et al, 2022; Suzuki et al, 2003).…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations